Effective Doping of Square/Octagon‐Phase Arsenene by Adsorption of Organic Molecules. Issue 5 (27th March 2021) - Zhao, Ning; Schwingenschlögl, Udo
Abstract: Adsorption of organic molecules can be a better choice than traditional chemical doping to achieve effective doping of 2D materials. The adsorption of organic molecules on square/octagon‐phase (S/O‐phase) arsenene is investigated and promoted the possibility of developing p–n junctions. In particular, it is found that adsorption of F4‐TCNQ or TCNE molecules leads to effective p‐doping. Adsorption of DMPD or TTF molecules leads to less effective n‐doping. Interestingly, in the case of TTF adsorption strain engineering can be used to greatly improve the material properties. Therefore, both effective n‐ and p‐doping of S/O‐phase arsenene can be realized. Abstract : It is shown that both n‐ and p‐doped square/octagon‐phase arsenene can be realized by molecular doping, opening a route to developing p–n junctions. For example, F4‐TCNQ gives rise to shallow p‐doping (0.08 eV) combined with low hole effective mass. In the case of n‐doping the material performance can be efficiently improved by application of strain.